Konflik Batin Tokoh Livka dalam Novel Ingkar Karya Boy Candra: Kajian Psikologi Sastra - Vivi Erinsyah Br Ginting; Haris Sutan Lubis; Emma Marsella (Bahasa Indonesia Prima, 2024)
This study aims to describe the inner conflict of Livka's character in the novel Ingkar by Boy Candra. The method used is descriptive qualitative with simak catat technique. The theory applied is Kurt Lewin's conflict theory, which divides inner conflict into three types: (1) near-close conflict, which is when a person is faced with two positive choices; (2) near-far conflict, where one choice has both positive and negative aspects; and (3) far-far conflict, which is when a person is faced with two negative choices. The analysis was conducted by presenting, classifying, categorizing, and summarizing the data. The results show that Livka's character faces all three types of conflict in the novel Ingkar.